2021
DOI: 10.1002/jimd.12384
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of urea cycle disorders: Report from a nationwide study in Japan

Abstract: Urea cycle disorders (UCDs) are inherited metabolic disorders with impaired nitrogen detoxification caused by defects in urea cycle enzymes. They often manifest with hyperammonemic attacks resulting in significant morbidity or death. We performed a nationwide questionnaire-based study between January 2000 and March 2018 to document all UCDs in Japan, including diagnoses, treatments, and outcomes. A total of 229 patients with UCDs were enrolled in this study: 73 males and 53 females with ornithine transcarbamyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…25 We previously reported that neonatal onset UCD patients, who often develop severe hyperammonemia (≥360 μmol/L), should receive LT to prevent frequent hyperammonemia attacks and to improve their QOL, and that even such patients may achieve almost normal neurodevelopmental outcome after LT. 3 In the present study, there is no significant difference in long-term survival between UCD patients with and without LT because the long-term survival in UCDs patients without LT also is improved compared to our previous study. 26 In the recent years, clinicians in Japan have more information on UCDs and novel treatments such as sodium phenylbutyrate and citrulline were more commonly administered. Long-term management skills for patients with UCDs were progressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 We previously reported that neonatal onset UCD patients, who often develop severe hyperammonemia (≥360 μmol/L), should receive LT to prevent frequent hyperammonemia attacks and to improve their QOL, and that even such patients may achieve almost normal neurodevelopmental outcome after LT. 3 In the present study, there is no significant difference in long-term survival between UCD patients with and without LT because the long-term survival in UCDs patients without LT also is improved compared to our previous study. 26 In the recent years, clinicians in Japan have more information on UCDs and novel treatments such as sodium phenylbutyrate and citrulline were more commonly administered. Long-term management skills for patients with UCDs were progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Improved hemodialysis techniques in neonates have resulted in a more widespread use of this highly efficient modality. 26 For long-term neurodevelopmental outcome, patients with hyperammonemia ≥360 μmol/L at the onset time may not achieve normal neurodevelopmental outcome even after receiving LT likely because of the impact of initial blood ammonia levels on brain. However, this study suggested that ASSD patients when receiving early LT, and despite severe hyperammonemia (≥360 μmol/L) at the onset time, might be expected to achieve normal neurodevelopmental outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, we invited 1009 medical institutions, including the respective departments of pediatrics, endocrinology and metabolism, neonatology, genetics, and transplant surgery, to participate in a questionnaire survey regarding patients with citrin deficiency (Data S1). Each institution was a medical center that serviced a local area in Japan and had approximately 300 beds, based on previous survey reports 21 . The questionnaire aimed to establish whether healthcare professionals had diagnosed or provided medical treatment to patients with citrin deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Each institution was a medical center that serviced a local area in Japan and had approximately 300 beds, based on previous survey reports. 21 The questionnaire aimed to establish whether healthcare professionals had diagnosed or provided medical treatment to patients with citrin deficiency. Of the 1009 institutions, 731 (72%) responded, and 104 confirmed that patients with citrin deficiency had been diagnosed and/or treated at their facility.…”
Section: Study Participantsmentioning
confidence: 99%